Ontogeny of Intestinal Epithelial Innate Immune Responses - Hornef, Mathias W.; Fulde, Marcus (Frontiers in Immunology, 2014)
Emerging evidence indicates that processes during postnatal development might significantly influence the establishment of mucosal host-microbial homeostasis. Developmental and adaptive immunological processes but also environmental and microbial exposure early after birth might thus affect disease susceptibility and health during adult life. The present review aims at summarizing the current understanding of the intestinal epithelial innate immune system and its developmental and adaptive changes after birth.